(3GdNdjL GdYQHj ef NdGd fUhU GdQMGdjf hGdeDQNjf GdHQJZGdjjf EHGf YUQ GdcTha GdLZQGajI GdcHQi hGdGMJdGd GdHQJZGdj ddNdjL, (B1507-1650 (3e (B:s (3fUhU hCHMGK fGOQI (B/s - (3EjHT, CMeOs ((3CHh XHj (B:s (3OGFQI GdKbGaI hGdSjGMI,s (3OGQ GdcJH GdhWfjI,s (3GdeLeY GdKbGaj,s [(3ecGf GdfTQ ZjQ eMOO(B] :s (3EUOGQGJs, 2019)
(3efP YUQ GdcTha GdLZQGajI GdcHQi (B((3ChGNQ GdbQf GdNGeS YTQ ddejdGO(B)(3, hYdi GeJOGO aJQI GdGMJdGd GdHQJZGdj ddNdjL GdYQHj (B(1507- 1650(3e(B)(3, cJH YOO ef GdQMGdjf hGdeDQNjf GdHQJZGdjjf Yf GdefWbI hCMOGKgG, hJQchG hKGFb hfUhUG aj ZGjI GdCgejI, hjJfGhd gPG GdcJGH Ydi eLehYI fGOQI hHGdZI GdCgejI JJCda ef (B30 (3fUG hHMKG HQJZGdjG, JQLY Edi ChGNQ GdbQf GdNGeS YTQ hMJi GdfUa GdChd ef GdbQf GdSGHY YTQ ddejdGO(B.s
(3UhQI GdZdGa (B: (3CSQi MQH GdHQJZGdjjf jbhehf HHfGA MUf, fbjTI ghdfOjI ef GdbQf GdSGHY YTQ ; JfajP GdZdGa (B: (3eMeO eQYj(B.s
(3jJhGaQ HGdecJHI (B: (3eLdO (B1-3.s
Keywords: (3GdNdjL GdYQHjs -- (3JGQjNs -- (3GdGMJdGd GdHQJZGdj, (B1507-1650s; (3GdNdjL GdYQHjs -- (3hUa hQMdGJs -- (3GdGMJdGd GdHQJZGdj, (B1507-1650 s